Experimental, Pathologic, and Clinical Findings of Radiofrequency Catheter Ablation of Para-Hisian Region From the Right Ventricle in Dogs and Humans. (June 2017) - Xue, Yumei; Zhan, Xianzhang; Wu, Shulin; Wang, Hongyue; Liu, Yang; Liao, Zili; Deng, Hai; Duan, Xuejing; Zeng, Shaoying; Liang, Dongpo; Elvan, Arif; Fang, Xianhong; et al.
Abstract : Background—: Ablation of para-Hisian accessory pathway (AP) poses high risks of atrioventricular block. We developed a pacing technique to differentiate the near-field (NF) from far-field His activations to avoid the complication. Methods and Results—: Three-dimensional mapping of the right ventricle was performed in 15 mongrel dogs and 23 patients with para-Hisian AP. Using different pacing outputs, the NF- and far-field His activation was identified on the ventricular aspect. Radiofrequency application was delivered at the NF His site in 8 (group 1) and the far-field His site in 7 dogs (group 2), followed by pathologic examination after 14 days. NF His activation was captured with 5 mA/1 ms in 10 and 10 mA/1 ms in 5 dogs. In group 1, radiofrequency delivery resulted in complete atrioventricular block in 3, right bundle branch block with HV (His-to-ventricular) interval prolongation in 1, and only right bundle branch block in 2 dogs, whereas no changes occurred in group 2. Pathologic examination in group-1 dogs showed complete or partial necrosis of the His bundle in 4 and complete necrosis of the right bundle branch in 5 dogs. In group 2, partial necrosis in the right bundle branch was found only in 1 dog. Using this pacing technique, the APs were 5.7±1.2 mm away from the His bundle located superiorly in 20 or inferiorly in 3 patients. All APs were successfully eliminated with 1 to 3 radiofrequency applications. No complications and recurrence occurred during a follow-up of 11.8±1.4 months. Conclusions—: Differentiating the NF His from far-field His activations led to a high ablation success without atrioventricular block in para-Hisian AP patients. Abstract : Supplemental Digital Content is available in the text.